Macroeconomic determinants of stock market volatility: Evidence from post socialist countries - Damiran, Suvdaa; Dorjdagva, Odbileg; Sukhee, Batbileg; Myagmarsuren, Tsevelmaa (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This paper aims to estimate macroeconomic determinants of stock market volatility (SMV) for post-socialist countries using unbalanced panel data from 1995 to 2020. We evaluated the impacts of the stock market and macroeconomic determinants on SMV using the Feasible Generalized Least Squares (FGLS) model based on the data of selected eleven post-socialist countries in terms of two consecutive years. The findings reveal that economic freedom has a strong and good impact at any time; however, although the previous year’s turnover ratio (TOR) had a positive impact, it has an unfavorable impact on SMV in the current year. Furthermore, the year’s inflation rate, level of corruption, economic growth rate, and stock market value have all shown a negative impact. The study’s findings serve as a useful reference for stock market practitioners and policymakers in these nations in making decisions.